BPK FINDINGS TRENDS ON INTERNAL CONTROL SYSTEMS IN LOCAL GOVERNMENT FINANCIAL STATEMENTS - Leka, Earlyanzen Mustika; Sutopo, Bambang (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
Abstract This study investigates the trends and distribution of weaknesses in the Government Internal Control System (SPIP) based on audit findings from the Audit Board of the Republic of Indonesia (BPK) on the Local Government Financial Statements (LKPD) during the period 2019–2023. The research employs quantitative descriptive analysis and ANOVA testing to examine patterns and identify whether there are statistically significant differences in the occurrence of internal control weaknesses across the five-year span. The results reveal that the most dominant weaknesses were found in the element of control activities, especially in the execution of expenditures that did not comply with regulations, inaccurate or incomplete accounting records, and ineffective internal supervision. In addition, weaknesses in the control environment—such as incomplete standard operating procedures (SOPs), lack of proper segregation of duties, and suboptimal functioning of internal inspectorates—persisted across the observed years. The ANOVA test showed no statistically significant differences between the years (P-value > 0.05), indicating limited effectiveness of implemented improvements. These findings emphasize the urgency of strengthening the internal control system comprehensively through institutional reform, enhanced monitoring capacity, increased professionalism of personnel, and integration of information technology to promote transparency, accountability, and sustainable financial governance in local governments.